Estimator design for complex networks with encoding decoding mechanism and buffer-aided strategy: A partial-nodes accessible case - Zhang, Yuhan; Zou, Lei; Wang, Yezheng; Wang, Yu-Ang (ISA transactions, 2022)
This article focuses on the partial-nodes-based state estimation (PNBSE) issue for a complex network with the encoding-decoding mechanism (EDM) over the unreliable communication channel, where the signals are transmitted in an intermittent manner. A so-called EDM is exploited to convert the transmitted signals into a set of codewords with finite bits so as to facilitate the transmission efficiency between the complex networks and the estimator. To guarantee the state estimation (SE) performance subject to the intermittent communication nature of the channel, a buffer with limited capacity, which stores the recent measurement signals and sends them to the estimator simultaneously, is adopted to improve the utilization rate of the measurement signals in the estimation process. The main objective of the investigated problem is to construct a partial-nodes-based (PNB) estimator to generate the desired state estimates for the underlying complex networks. Considering the intermittent feature of signal transmission, the ultimate boundedness of the SE error under the constructed PNB estimator is discussed, and then, sufficient conditions are derived which ensure that the desired PNB estimator exists. An simulation example is given to confirm the correctness and effectiveness of the proposed estimator design strategy in the end. •For the first time, the ultimately bounded state estimation problem is investigated for the PNB complex network with encoding-decoding mechanism subject to unreliable communications.•A novel partial-nodes-based state estimator with buffer-aided strategy is proposed to guarantee the desired estimation performance.